Analysis of oxygen uptake kinetics and heart rate kinetics in competitive swimmers - On- and Off-kinetics response at lactate threshold intensity - Sengoku, Y.; Sano, M.; Narita, K.; Tsubakimoto, S. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this study was to investigate oxygen up-take (VO2) and heart rate (HR) kinetics during swimming exercise at lactate threshold intensity, and to clarify the association of these parameters with endurance capacity and performance. After previous determination of VO2max, swimming velocity at VO2max (v VO2max) and swimming velocity at lactate threshold (vLT), nine highly trained male swimmers were divided into two groups according to their specialized swimming event: sprint event (SP group) and middle distance (MD group). Participants performed a 12 min swimming exercise in a swimming flume that consisted of 4 min at 70% vLT, 4 min at 100% vLT intensity swimming, and 4 min at 70% vLT. On-kinetics of VO2 and HR were investigated at the commencement of the 100% vLT period, and Off-kinetics were investigated at the second 4 min 70% vLT period. All tests were conducted using the front-crawl swimming style with breath-by-breath and beat-by-beat analysis using specific snorkel (Metaswim, Cortex) and HR monitors (RCX5, Polar), respectively. Mono-exponential functions were utilized to obtain each kinetics variable. The MD group presented significantly shorter time constants of HR On-kinetics than the SP group (SP group at 66.3 ± 21.2 sec vs. MD group at 37.1 ± 5.8 sec, p < .05). HR On-kinetics correlated significantly with endurance performance (v VO2max, r = -0.840, p < 0.01; vLT, r = -0.672, p < 0.05). Statistical differences and correlations were not observed with VO2 kinetics variables. Our results suggest that HR kinetics, but not VO2 kinetics variables are related to endurance capacity at lactate threshold swimming intensity.